Transdisciplinarity as a Methodological Strategy for the Promotion of Rights with Adolescents in a Social Outreach Project at the University of Costa Rica - Artavia Fallas, Cindy (2025)
This article aims to analyze the scope and limitations of transdisciplinarity as a methodological strategy for promoting rights among adolescents within the framework of the social action project TC-427, Interdisciplinary Team for the Promotion of Rights and Comprehensive Development of Adolescents, carried out by the Teacher Training School of the University of Costa Rica from 2019 to 2023. The project employs a qualitative methodology, oriented toward participatory action research, integrating phases of exploration, process planning, experimentation, and systematization. Initially, the article reviews the project's history to understand its evolving approach and the involvement of various disciplines in its development. The subsequent section systematizes and integrates the actions undertaken by the work team (comprising students and the coordinator) to promote the rights of adolescents, the target beneficiaries of this project. The article also reflects on the outcomes of the work conducted in recent years, assessing the scope and limitations of transdisciplinary methodology within the context of social outreach projects. The findings suggest that transdisciplinary work has fostered learning through collaborative efforts and knowledge exchange among students, transforming the project into a space not only for building professional knowledge but also for effecting social change.